Antagonistic mechanisms of fluorescent pseudomonads against Phytophthora capsici in black pepper (Piper nigrum L.) - Sarma, Diby Paul, M Anandaraj, A Kumar, Y R (Journal of Spices and Aromatic Crops, 2005)
Fluorescent pseudomonads were selectively isolated from black pepper (Piper nigrum) roots and screened for volatile and non-volatile metabolite production and inhibition in growth of Phytophthora capsici, the causal organism of foot rot disease. Among the isolates tested, the inhibition of P. capsici varied from 36.3% to 70.0% by non-volatile metabolites and from 2% to 23% by volatile-metabolites. Isolate IISR-51 caused maximum inhibition of P. capsici by production of non-volatile and volatile metabolites. Many of the isolates produced hydrogen cyanide, which limited the growth of P. capsici. The study indicated the involvement of siderophore-mediated antagonism in fluorescent pseudomonads. The fluorescent pseudomonads could systemically invade black pepper cuttings upon root bacterization.